Determination of tissue and plasma concentrations of PTHrP in fish: development and validation of a radioimmunoassay using a teleost 1–34 N-terminal peptide - Rotllant, J. (2014)
A specific and sensitive radioimmunoassay (RIA) for the N-terminus of sea bream (Sparus auratus) and flounder (Platichthys flesus) parathyroid hormone-related protein (PTHrP) was developed. A (1–34) amino-terminal sequence of flounder PTHrP was synthesized commercially and used as the antigen to generate specific antiserum. The same sequence with an added tyrosine (1– 35Tyr) was used for iodination. Human (1–34) parathyroid hormone (PTH), human (1–34) PTHrP, and rat (1–34) PTHrP did not cross-react with the antiserum or displace the teleost peptide. Measurement of PTHrP in fish plasma was only possible after denaturing by heat treatment due to endogenous plasma binding activity. The minimum detectable concentration of (1–34) PTHrP in the assay was 2.5 pg/tube. The level of immunoreactive (1–34) PTHrP in plasma was 5.2 0.44 ng/ml (mean SEM, n ¼ 20) for flounder and 2.5 0.29 ng/ml (n ¼ 64) for sea bream. Dilution curves of denatured fish plasma were parallel to the assay standard curve, indicating that the activity in the samples was indistinguishable immunologically from (1–34) PTHrP. Immunoreactivity was present, in order of abundance, in extracts of pituitary, oesophagus, kidney, head kidney, gills, intestine, skin, muscle, and liver. The pituitary gland and oesophagus contained the most abundant levels of PTHrP, 37.7 6.1 ng/g wet tissue and 2.3 0.7 ng/g wet tissue, respectively. The results suggest that in fish PTHrP may act in a paracrine and/or autocrine manner but may also be a classical hormone with the pituitary gland as a potential major source of the protein.